Development Of Starch-Based Imitation Cheese Spread - PPTI, Pusat Pengajian Teknologi Industri (Universiti Sains Malaysia, 2021)
The aim of this study was to develop starch-based imitation cheese spread as an alternative imitation cheese product to replace its dairy counterpart. The effects of different weight percentages of glycerol monostearate (GMS) (0.0%, 2.5%, 5.0%, 7.5% and 10.0%) in the starch-based imitation cheese spread on the physicochemical and rheological properties were studied. The products prepared were characterized in terms of proximate composition, colour, oil separation, viscoelastic behaviour and spreadability. Starch-based imitation cheese spread with different weight percentages of GMS had significant effects (p < 0.05) on the moisture and fat content in proximate analysis. Results showed that increasing GMS amount significantly increased the lightness and decreased chromaticity of the starch-based imitation cheese spread produced. Samples containing GMS were found to remain stable without oil separation upon storage. Besides, solid-like behaviour was displayed by all samples except the sample formulated with 0.0% GMS. The findings indicated that the presence of GMS had a direct effect on the viscoelastic behaviour of the starch-based imitation cheese spread. With increased weight percentage of GMS up to 10.0%, both storage (G′) and loss (G″) moduli were increased significantly. Increasing GMS content resulted in a significant (p < 0.05) decrement in spreadability of the starch-based imitation cheese spread. Overall, results revealed that modifying GMS content alone was not adequate to imitate properties of dairy-based cheese spread product, thus further studies on other factors are warranted.